The Laudare School : the quest for excellence in the inner-city - Truscott, Ashley (SAGE knowledge. Cases., 2016)
In early January 2013, Adrian Miller, principal of the Laudare School, situated close to the inner-city in the lower-income suburb of Belmont in Johannesburg, was reading through the results of a recent customer satisfaction survey. While the feedback from parents and pupils was generally positive, it also highlighted some areas that needed attention, particularly the challenges of running a private school in an inner-city environment. Furthermore, with scarce resources it was difficult to grow and develop the school into one that offered an excellent educational experience. Miller wondered how he could ensure that the school offered its pupils, teachers, and parents a service that was in line with his vision.